2019
DOI: 10.1038/s41397-019-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

DPYD*6 plays an important role in fluoropyrimidine toxicity in addition to DPYD*2A and c.2846A>T: a comprehensive analysis in 1254 patients

Abstract: Dihydropyrimidine dehydrogenase (DPYD) is a highly polymorphic gene and classic deficient variants (i.e., c.1236G>A/HapB3, c.1679T>G, c.1905+1G>A and c.2846A>T) are characterized by impaired enzyme activity and risk of severe adverse drug reactions (ADRs) in patients treated with fluoropyrimidines. The identification of poor metabolizers by pre-emptive DPYD screening may reduce the rate of ADRs but many patients with wild-type genotype for classic variants may still display ADRs. Therefore, the search for addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 43 publications
4
33
1
Order By: Relevance
“…Additionally, 6 patients with a single DPYD*9A mutation, 14 with a single DPYD*5 mutation and 4 with a single DPYD*6 mutation were all documented to have severe toxicity. A recent large study of 1254 patients also found a significant association between DPYD*6 and severe 5-FU toxicity [ 20 ]. We also recorded 31 patients who had more than one DPYD gene variant.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 6 patients with a single DPYD*9A mutation, 14 with a single DPYD*5 mutation and 4 with a single DPYD*6 mutation were all documented to have severe toxicity. A recent large study of 1254 patients also found a significant association between DPYD*6 and severe 5-FU toxicity [ 20 ]. We also recorded 31 patients who had more than one DPYD gene variant.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of fluoropyrimidine involves enzymes with different intermediate metabolites, prevalently depending on the key enzyme DPD, that metabolize >80% administered 5-FU or capecitabine dose into 5-fluoro-5,6-dihydrouracil (5-FDHU). 27 In the event of DPD inactivation or reduced effectiveness, the 5-FU amount for activation of anabolic pathway increases, inducing adverse effects.…”
Section: Fluoropyrimidines and Clinically Relevant Dpyd Genetic Variantsmentioning
confidence: 99%
“…The authors suggested more investigation for c.1236G>A and c.2846A>T carriers and adequate dose modulation 50% vs 25%. 1896T>C, and c.2194G>A variants were detected in a population of 982 patients who experienced ≥G2 gastrointestinal and/or ≥G3 hematological adverse events, and in a cohort of 272 patients not requiring reduction of drug dose, treatment delay, or discontinuation; while c.1905+1G>A and c.2846A>T were reported only in the cohort of patients experiencing LT 27. DPYD c.1679T>G In an univariate analysis, DPYD*2A c.1905+1G>A, c.2846A>T, and c.2194G>A alleles were reported as significantly correlated with hematological and gastrointestinal adverse events (P<0.05); c.496A>G variant was associated with neutropenia (P=0.06).…”
mentioning
confidence: 95%
“…Based on the recent recommendation of the (European Medicines Agency (EMA); EMA/125891/2020) and AIFA (Italian Medicines Agency; AIFA 2020.05.25) Pharmacovigilance Risk Assessment Committee, all patients who are candidates for fluoropyrimidine treatment should be tested for dihydropyrimidine dehydrogenase (DPYD) to prevent potentially serious adverse events. The working group recommends the analysis of the following mutations: c.1236G>A (c.1129-5923C>G), c.1679T>G, c.1905+1G>A and c.2846A>T. 91 Furthermore, it may be useful to consider additional variants such as c.2194G>A in case of toxicity during treatment [92][93][94][95][96] (table 3).…”
Section: Adjacent Infiltrated Organs Have To Be Resected In Blockmentioning
confidence: 99%